Science Perspectives for 3D Spectroscopy: Proceedings of the ESO Workshop held in Garching, Germany, 10 - 14 October 2005 - Kissler-Patig, Markus; Roth, Martin M.; Walsh, Jeremy R. (Eso Astrophysics Symposia European Southern Observatory, 2007)
This volume contains the proceedings of possibly the last conference ever on integral-field spectroscopy. The contributors, noted authorities in the field, focus on the scientific questions that can be answered with integral-field spectroscopy, ranging from solar system studies all the way to high redshift surveys. Overall readers get a state-of-the-science review of astronomical 3D spectroscopy.